Effect of initial emergency room imaging choice on time to hip reduction and repeat imaging. Issue 3 (March 2019) - Walker, Matthew R.; El Naga, Ashraf N.; Atassi, Omar H.; Perkins, Christopher H.; Mitchell, Scott A.
Highlights: The shift toward initial CT scanning at our institution has led to increased radiation exposure from repeat CT scans. The shift toward initial CT scanning at our institution has led to avoidable delays in the reduction of hip dislocations. We recommend that the AP pelvis x-ray remain part of the initial trauma assessment, consistent with current ATLS protocol. Abstract: Objectives: Hip dislocations are highly morbid injuries necessitating prompt reduction and post-reduction assessment for fracture and incarcerated fragments. Recent literature has questioned the need for initial pelvic radiographs for acute trauma patients, resulting in computed tomography (CT) scans as the initial evaluation. This study investigates the relationship between choice of pre-reduction imaging and treatment of acute hip dislocations. Design: Retrospective Case-Control. Setting: Single Academic Level I Trauma Center. Methods: All acute hip dislocations from 2011 to 2016 were reviewed. Exclusion criteria were diagnosis of dislocation at another facility, death prior to reduction, emergent surgical or ICU intervention, and periprosthetic dislocation. Patients were grouped by those with only a radiograph prior to reduction, Group I, versus those with a pre-reduction CT scan, Group II. The primary outcomes were time to reduction and the acquisition of a second CT scan. Results: Of the 123 hip dislocations identified, 35 patients were excluded, mostly for transfer with a known dislocation. Group I included 29 patients and Group II included 59 patients. The mean time to reduction was 74 min in Group I and 129 min in Group II for a difference of 55 min (p < 0.001). The rate of repeat CT scan was 0 in Group I versus 48 (81%) in Group II (p < 0.001). Conclusion: Initial trauma pelvic radiography prior to CT is still important in the setting of suspected hip pathology to decrease time to hip reduction and unnecessary radiation exposure. Level of evidence: Prognostic Level III.